Die regionalen Rates of Return der öffentlichen Hochschulfinanzierung - Rosner, Ulf; Weimann, Joachim (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
This article examines the short-term regional economic effect of universities. The methodology used differs substantially from previous studies as it focuses on the additional resources attracted to the region by the establishment of universities. The effects of the attracted resources are therefore related to the basic financing provided by the federal state (Land). We call these relations the regional rates of return on university financing. We demonstrate the regional rates of return using the experience of the Otto-von-Guericke-University Magdeburg and the college of higher education Magdeburg-Stendal as examples. The results indicate that the financing of universities is an effective means to create both jobs and economic prosperity. In turn, the reduction of public funding for universities causes substantial opportunity costs for the region, even in the short term.